An interpretive approach to investigating the facilitation of electronically supported distribution teamwork: Some preliminary results - Jarman, Rodney; Atkinson, Douglas; Pervan, Graham (School of Information Management and Systems, Monash University, 1999)
Over the last ten years there have been rapid developments in the electronic technologyavailable to support group work. This has included technology to support groups whosemembers are geographically separate. This electronic technology has been labelled groupsupport systems (GSS). GSS has been shown to provide a number of benefits to groupsarising out of features such as parallel processing, structured decision making processes andovercoming time barriers. Research into face-to-face GSS-supported teamwork has shownfacilitation is an important factor to the success of the interaction. It is likely this is also trueof GSS-supported distributed teamwork. Despite this importance there has been littleresearch into this area. This paper reports on a study which seeks to identify and evaluateinterventions that can facilitate distributed teamwork supported by GSS. The paperdiscusses how the research is based on an interpretive research approach and why this isparticularly effective for researching facilitation. It concludes with a discussion of somepreliminary findings which support the need for facilitation in a distributed environment andthe efficacy of an interpretive approach for facilitation research